2000
DOI: 10.1148/radiology.216.3.r00se07803
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-enhanced MR Imaging of Uterine Cervical Cancer: Pharmacokinetic Analysis with Histopathologic Correlation and Its Importance in Predicting the Outcome of Radiation Therapy

Abstract: Areas of increased contrast enhancement are mainly composed of abundant cancer cell fascicles, whereas poorly perfused areas are composed of fibrous tissue with scattered cancer cells. Radiation therapy is more effective in well-enhanced tumors, resulting in improved local control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 21 publications
5
94
1
2
Order By: Relevance
“…As no other imaging parameters correlated with staging, the current findings indicate the potential of nABC as a predictor of tumor stage. A high local nABC may indicate a well-vascularized region of high oxygen pressure (pO 2 ), most likely with proliferating cells, which also has been argued previously for comparable parameters derived from DCEMRI [1,10,18,19]. Thus, it may be that low levels of nABC indicate hypoxia, and that nABC maps may be employed in biological image adapted radiotherapy.…”
Section: Discussionsupporting
confidence: 54%
“…As no other imaging parameters correlated with staging, the current findings indicate the potential of nABC as a predictor of tumor stage. A high local nABC may indicate a well-vascularized region of high oxygen pressure (pO 2 ), most likely with proliferating cells, which also has been argued previously for comparable parameters derived from DCEMRI [1,10,18,19]. Thus, it may be that low levels of nABC indicate hypoxia, and that nABC maps may be employed in biological image adapted radiotherapy.…”
Section: Discussionsupporting
confidence: 54%
“…The role of pretreatment DCE-MR imaging in predicting therapeutic response in colorectal and cervical cancers has been reported previously. [26][27][28] From a DCE-MR imaging study of patients with uterine cervical cancer undergoing surgery, Yamashita et al 26 reported that areas of high K trans were predominantly composed of cancer cell fascicles, whereas areas of low K trans were composed of fibrous tissue with scattered cancer cells. Furthermore, radiation therapy was more effective in tumors with high K trans than in tumors exhibiting low K trans values.…”
Section: Discussionmentioning
confidence: 99%
“…35,49 Dynamic imaging also has been advocated as an aid in predicting tumor response to radiotherapy. [51][52][53] MRI also has been shown to be a cost-effective staging technique. Hricak et al 54 reported that patients with cervical cancer who underwent MRI as the initial imaging procedure for staging required fewer tests and procedures compared with those who underwent standard clinical staging.…”
Section: Mrimentioning
confidence: 99%